Intellectual capital reporting in Malaysian technology industry - Azlina Rahim,; Ruhaya Atan,; Amrizah Kamaluddin, (FEP, 2011)
In recent decades, Malaysia has witnessed tremendous economic and social changes. As a result, the business environment is also becoming more complex and demanding. One of the areas that captured the attention of the accounting profession was intellectual capital reporting. Previous studies revealed that intellectual capital reporting has a major impact on investor’s confidence. Due to the importance of intellectual capital, its disclosure is significant. The purpose of this paper is to investigate the intellectual capital reporting practices of Malaysian listed companies in the technology industry. This study also assesses the association of firm’s characteristics and intellectual capital disclosure. Using the content analysis method, it reviews the annual reports of all the technology companies listed on the Main Market and Ace Market of Bursa Malaysia in year 2009. The study reveals that the technology industry discloses most on external capital compared to human capital and internal capital. There is not much difference in terms of intellectual capital disclosure between the Main Market and the Ace Market. However, for the technology industry the firm’s characteristics does not have any association with the extent of intellectual capital reporting. Since the study focuses on one industry, the results of this study may assist the companies to be more aware of other aspects of corporate reporting particularly concerning intellectual capital disclosure. In addition, it may benefit the regulators and standard setting bodies for future regulatory impact especially in establishing an intellectual capital reporting framework for Malaysian companies.